Long-term forgetting is independent of age in healthy children and adolescents - Pellegrini, Felizia; Uebelhardt, Nina; Bigi, Sandra; Studer, Martina; Nocco, Luana; Wingeier, Kevin; Lidzba, Karen (Frontiers in Psychology, 2024)
In clinical neuropsychology, the phenomenon of accelerated long-term forgetting (ALF) has advanced to be a marker for subtle but clinically relevant memory problems associated with a range of neurological conditions. The normal developmental trajectory of long-term memory, in this case memory recall after one week, and the influence of cognitive variables such as intelligence have not extensively been described, which is a drawback for the use of accelerated long-term forgetting measures in pediatric neuropsychology.In this clinical observation study, we analyzed the normal developmental trajectory of verbal memory recall after one week in healthy children and adolescents. We hypothesized that one-week recall and one-week forgetting would be age dependent and correlate with other cognitive functions such as intelligence and working memory. Sixty-three healthy participants between the age of eight and 16 years completed a newly developed auditory verbal learning test (WoMBAT) and the WISC-V intelligence test (General Ability Index, GAI). Using these tests, one week recall and one week forgetting have been studied in relation to GAI, verbal learning performance and verbal working memory.Results: Neither one week recall nor one week forgetting seem to be age dependent. They are also not significantly predicted by other cognitive functions such as GAI or working memory. Instead, the ability to recall a previously memorized word list after seven days seems to depend solely on the initial learning capacity.In the clinical setting, this finding can help interpreting difficulties in free recall after seven days or more, since they can probably not be attributed to young age or low intelligence.